AKAD WAKALAH DALAM INVESTASI SYARIAH: TANTANGAN DAN PELUANG - Barokallah; Miti Yarmunida; Nenan Julir (Jurnal Aghniya, 2026)
Investors must know the contracts used when making an investment agreement to minimize losses on investments made, if the investor enters into an agreement granting authority to the investment manager to manage funds entrusted to the customer with the aim of making a profit. Research conducted regarding the analysis of wakalah contracts provides an overview of a number of important problems such as the lack of knowledge of investors who are just starting to invest. This type of research uses a qualitative type with descriptive research methods. Choosing the right contract depends on the type of investment chosen, the risks to be faced, and the relationship between the parties involved. Wakalah contracts offer flexibility and better risk management for representatives. In wakalah contracts, it is more advantageous for situations where professional and efficient management is required without transferring risk to the managing party. The wakalah contract has the advantage of being managed by a more professional person without transferring the risk to the manager. The wakalah contract makes it easier for the deputy to get solutions according to the problem.